Concentrations of cefixime in bronchial mucosa and sputum after three oral multiple dose regimens. Issue 5 (May 1990) - Baldwin, D R; Andrews, J M; Ashby, J P; Wise, R; Honeybourne, D
Abstract : In a study of 58 patients the concentrations of cefixime, a new oral cephem antibiotic, in bronchial mucosa were 35-40% of the concentrations found in simultaneously collected serum samples. The antibiotic was often undetectable in sputum despite a highly sensitive assay.